2009
DOI: 10.1177/112070000901900406
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Whole Blood Metal Ion Levels following Resurfacing: Serial Measurements in a Multi-Centre Study

Abstract: Seventy-seven patients implanted with unilateral resurfacing prosthesis were recruited from four centres. Serial whole blood samples were collected and ion levels were analysed. In most cases, the ion levels stabilized by 3 months. The 24 month median ion levels were 1.49ug/l for chromium and cobalt. In approximately 50% of patients the increase in chromium and cobalt level was less than 1ug/l. There were 6 patients with abnormally high metal ion levels. Of these 4 were significant outliers, had high ion level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
2
21
0
1
Order By: Relevance
“…The RHA implant that we used (ASR) was later withdrawn from the market due to excessive failure rates, but despite the fact that it included a rather large proportion of females and of heads below 51 mm, the median ion concentrations measured in the present study were comparable to those in other prospective RHA studies involving implants known to have either a high degree or a suboptimal degree of survival (Allan et al 2007, Heisel et al 2008, Daniel et al 2009, Isaac et al 2009, deSouza et al 2010, Garbuz et al 2010, Beaule et al 2011, Pattyn et al 2011). We therefore believe that our results are not specific for the ASR implant, but that they can be generally applied to metal ion and lymphocyte levels.…”
Section: Discussionsupporting
confidence: 68%
“…The RHA implant that we used (ASR) was later withdrawn from the market due to excessive failure rates, but despite the fact that it included a rather large proportion of females and of heads below 51 mm, the median ion concentrations measured in the present study were comparable to those in other prospective RHA studies involving implants known to have either a high degree or a suboptimal degree of survival (Allan et al 2007, Heisel et al 2008, Daniel et al 2009, Isaac et al 2009, deSouza et al 2010, Garbuz et al 2010, Beaule et al 2011, Pattyn et al 2011). We therefore believe that our results are not specific for the ASR implant, but that they can be generally applied to metal ion and lymphocyte levels.…”
Section: Discussionsupporting
confidence: 68%
“…One multicentre study involving a 24-month follow-up of 77 patients implanted with a unilateral resurfacing prosthesis found that ion levels were generally low and had stabilized by 3 months [15]. Six patients had abnormally high metal ion levels, and all of them also had a cup abduction angle above 55°.…”
Section: Discussionmentioning
confidence: 99%
“…These tend to stabilise three 55 to six months 54 after surgery. Research has shown that metal ion concentrations that are not directly cytotoxic to lymphocytes may affect events at a molecular level, thereby impeding lymphocyte proliferation 56 .…”
Section: Resultsmentioning
confidence: 96%